BSHI/BTS guidance on crossmatching before deceased donor kidney transplantation. (23rd September 2021) - Peacock, S.; Briggs, D.; Barnardo, M.; Battle, R.; Brookes, P.; Callaghan, C.; Clark, B.; Collins, C.; Day, S.; Diaz Burlinson, N.; Dunn, P.; Fernando, R.; et al.
Abstract: All UK H&I laboratories and transplant units operate under a single national kidney offering policy, but there have been variations in approach regarding when to undertake the pre‐transplant crossmatch test. In order to minimize cold ischaemia times for deceased donor kidney transplantation we sought to find ways to be able to report a crossmatch result as early as possible in the donation process. A panel of experts in transplant surgery, nephrology, specialist nursing in organ donation and H&I (all relevant UK laboratories represented) assessed evidence and opinion concerning five factors that relate to the effectiveness of the crossmatch process, as follows: when the result should be ready for reporting; what level of donor HLA typing is needed; crossmatch sample type and availability; fairness and equity; risks and patient safety. Guidelines aimed at improving practice based on these issues are presented, and we expect that following these will allow H&I laboratories to contribute to reducing CIT in deceased donor kidney transplantation.